Models of Teaching Reading Comprehension Applied by English Teacher of J-2 School In Academic Year 2016/2017 - Usadi, Ni Wayan Oktavia (Universitas Pendidikan Ganesha, 2017)
This research aimed to analyze the models that applied by the English teacher on J-2 SCHOOl. The subject was the English teachers and the students of J-2 in academic year of 2016/2017. This research was designed as descriptive research design. The researcher instruments are observation and interviewThe result of this study is the used of bottom-up and top models in teaching reading comprehension based on Grabe theory. The frequency of directive in first and second meeting the teacher taught with bottom-up model. The teacher used bottom-up model to teach the students with word meaning and the small particle part in reading comprehension. The third until five meeting was top-down model. The teacher would teach the students with a specific aspect, like teach the students about the specific of descriptive text. It could make students more critical about the text. The underlying reasons of English teacher apply models in teaching reading comprehension are to make the process of teaching English can run appropriately with the students level and the students can join the learning process efficiently. Bottom-up and top down model could make the students active and comfortable in the classroom.Â